Plumbing work for the planter boxes on the roof and in different floors within the building of BRAC University new campus project - Brac University (Brac University, 2023)
This record consists of general correspondence regarding plumbing work for the planter boxes on the roof and in different floors within the building of BRAC University new campus project.